The Influence of Student Perceptions on the Quality of Library Services and Learning Facilities in Increasing User Satisfaction in University Libraries - Khalid Lubis, Utama; Karman, Joni (SYNAPSI: Journal of Information Systems and Informatics Education, 2026)
Purpose of the study: This study aims to analyze the influence of students’ perceptions of library service quality and learning facilities on user satisfaction in university libraries, particularly at the Central Library of Universitas Negeri Yogyakarta (UNY).Methodology This study employed a quantitative ex-post facto approach involving 251 university students as respondents. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with SPSS for Windows. Instrument validity was tested using Pearson Product Moment, while reliability was tested using Cronbach’s Alpha. Classical assumption tests included normality, multicollinearity, and heteroscedasticity tests.Main Findings: The results showed that library service quality and learning facilities had positive and significant effects on user satisfaction both partially and simultaneously. Library service quality had the strongest influence on user satisfaction with a significance value of 0.000, while learning facilities also significantly influenced satisfaction with a significance value of 0.001. The coefficient of determination (R²) indicated that both variables contributed 43.2% to user satisfaction.Novelty/Originality of this study: The novelty of this study lies in the integration of library service quality and learning facilities into a single quantitative model for analyzing user satisfaction in university libraries. This research highlights the importance of modern learning facilities and digital-based services in supporting students’ academic experiences and positions university libraries as collaborative learning and digital literacy centers.